2009
DOI: 10.1021/nn800903p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Metal Oxides into Three-Dimensional Nanostructures: Synthesis and Application in Catalysis

Abstract: Nanostructured metal (Fe, Co, Mn, Cr, Mo) oxides were fabricated under microwave irradiation conditions in pure water without using any reducing or capping reagent. The metal oxides self-assembled into octahedra, spheres, triangular rods, pine, and hexagonal snowflake-like three-dimensional morphologies. Pine-structured nano-iron oxides were studied as a novel support for various catalytic organic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
200
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(204 citation statements)
references
References 76 publications
0
200
0
4
Order By: Relevance
“…Microwave-assisted chemical synthesis has several advantages over typical solvothermal process; reactions take place in minutes or hours which by solvothermal would take place in hours or days [45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted chemical synthesis has several advantages over typical solvothermal process; reactions take place in minutes or hours which by solvothermal would take place in hours or days [45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating has emerged as an alternative and powerful energy source for nanomaterial synthesis [23], which can accomplish chemical transformations in a short span of time (e.g., minutes instead of hours or days) since enough energy for the chemical reaction can be directly provided by molecular vibrations due to MW [24]. A variety of highly crystalline nanomaterials with uniform sizes such as titanium dioxide, copper, and iron oxides have been expeditiously synthesized in minutes [25][26][27]. The fusion of both the use of safer reagents and MW heating ideally suits the development of a sustainable technology to create noble nanometals of uniform, smaller size by reducing or eliminating the formation of undesired wastes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In catalysis, it is generally believed that, in addition to enhanced surface areas, NCMs often display interesting and unexpected properties that are qualitatively different from those of the corresponding bulk materials, or of the atomic or molecular species from which they are derived. 9 One well-known example is the use of gold for low temperature CO oxidation: bulk gold shows no activity, while gold nanoparticles (NPs) show high reactivity even at 77 K. [10][11][12] Defining and understanding the origin of the novel properties of NCMs has stimulated much research, and consequently, methods to prepare them have been extensively reported, both for metal oxides [13][14][15][16][17][18] and for noble metals. [19][20][21][22][23] Compared to the preparation of noble metal-based materials, the synthesis of metal oxide NCMs can be more complex, because some metals are very reactive toward oxygen, and agglomeration of oxide NPs occurs readily at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%